RESEARCH OF PRESSING PROCESS CONCRETE MIXTURES - Dudar, Igor; Dmytrenko, Viktoriya (Scientific Works of Vinnytsia National Technical University, 2015)
On the basis of thermal, dynamic analogy, the article suggests determining the speed of pressure distribution in concrete mixture by solving the differential equation of heat conductivity. It is suggested to characterize the speed of distribution of pressure in concrete mixture by the coefficient of barotropic. The influence of concrete property mixture on the value of parameter of barotropic was estimated.